The Pauline methodology of communicating the Word to a gentile audience - Dr. Mike Megrove Reddy (D.Litt.) (Africajournals, 2021)
The article describes and reconnoitres how the Apostle Paul, a Hebrew who was a welllearned man and a brilliant scholar and studentunder Gamaliel, went about conveying the Word to the Gentiles. The aim of this brief study is thus to describe the methodology used by the Apostle Paul to communicate the Word. He was raised to leadership and mentorship and gave guidance to the body of Christ and used every form of communication at his disposal to share the gospel with the surrounding Gentile world. Though he was called to preach the word of God to the Gentiles, he also preached to the Jews and defended the gospel against various kinds of obstinate and pagan rulers. The New Testament (Ἡ Καινὴ Διαθήκη) has a compilation of the letters written by the Apostle Paul. It should also be noted that although he was a prolific writer and teacher of the word, Paul encountered many barriers when it came to sharing the gospel. He was nonetheless very able to connect with people in the Graeco-Roman world outside of his culture and could easily communicate with the intellectual élites he encountered in the Empire. He was an eloquent speaker and also engaged effectively with the non-believers in the promulgation of the gospel message. Paul allowed both give-and-take, he was always eager to answer acute questions on faith issues, and he exerted himself in aiding people to acknowledge the truth of Jesus Christ. At times Paul spent a short period of time in a city, presenting the gospel and opening new churches. However, in Acts 18:11, it is evident that Paul stayed at one place for up to a year and time was spent in instructing the locals and also in evangelizing. This was clearly a sound strategy designed to meet his objective. In the Graeco-Roman culture, Paul personified a strong voice present in his oral and written works. The theoretical framework used in this study was the Shannon and Weaver Communication Model. This paper was based on a desktop research approach and literature from various sources was used including holy scriptures, academic articles, books, and various online sources.